2018
DOI: 10.1111/gbb.12521
|View full text |Cite
|
Sign up to set email alerts
|

Observational fear behavior in rodents as a model for empathy

Abstract: Empathy enables social mammals to recognize and share emotion with others and is well‐documented in non‐human primates. During the past few years, systematic observations have showed that a primal form of empathy also exists in rodents, indicating that empathy has an evolutionary continuity. Now, using rodents exhibiting emotional empathy, the molecular and cellular study of empathy in animals has begun in earnest. In this article, we will review recent reports that indicate that rodents can share states of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 107 publications
(278 reference statements)
1
34
0
Order By: Relevance
“…Consistent with these findings, we also noted significant increases in the percentage of immobility time among observer mice that viewed demonstrator mice with excessive immobility due to fear learning. This result is in accordance with previous findings regarding the fear observation system [33]. However, it remains unclear whether immobility among observer mice is due to empathy or conformity for the demonstrator.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with these findings, we also noted significant increases in the percentage of immobility time among observer mice that viewed demonstrator mice with excessive immobility due to fear learning. This result is in accordance with previous findings regarding the fear observation system [33]. However, it remains unclear whether immobility among observer mice is due to empathy or conformity for the demonstrator.…”
Section: Discussionsupporting
confidence: 93%
“…In the last decade, paradigms designed to investigate indirect fear conditioning in laboratory rodents have rapidly emerged in the literature [33]. However, in these observation systems, it remains unclear whether the observer mouse truly recognises the movements of and empathises with the demonstrator mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Observational fear is induced by social transmission of the demonstrator animal's affective state and should therefore be dependent on social perception and integrated social cognitive processes (Jeon et al, 2010;. By definition, this process, in which recognition of the demonstrator's distress triggers fear in the observer, is a form of affective (emotional) empathy and is a critical factor in the transmission of social fear (Jeon et al, 2010;Kim et al, 2019;Panksepp and Lahvis, 2011). Indeed, studies in primates and humans have demonstrated that stronger vicar-ious fear responses were positively associated with trait empathy (Kleberg et al, 2015;Olsson et al, 2016).…”
Section: Conceptual and Empirical Similarities Between Observational mentioning
confidence: 99%
“…Emotional contagion, i.e. the capacity to experience and share the emotions of others, is considered an evolutionary well-preserved mechanism that helps individuals to survive, not only in a dangerous savanna, but also within social groups (Preston and De Waal, 2001;de Waal, 2008;Kim et al, 2019) . Rodents, like many other animals, experience and learn from emotional contagion, as shown in studies on emotional contagion for pain (Church, 1959;Langford, 2006;Langford et al, 2010;Atsak et al, 2011;Pereira et al, 2012;Li et al, 2014;Cruz et al, 2020) and observational fear conditioning (Kavaliers et al, 2003;Jeon et al, 2010;Kim et al, 2010;Allsop et al, 2018;Keum and Shin, 2019;Nomura et al, 2019).…”
Section: Introductionmentioning
confidence: 99%